Business cycle effects of credit and technology shocks in a DSGE model with firm defaults - Hashem Pesaran; TengTeng Xu (Institute for the Study of Labor (IZA), 2011)
This paper proposes a theoretical framework to analyze the impacts of credit and technology shocks on business cycle dynamics, where firms rely on banks and households for capital financing. Firms are identical ex ante but differ ex post due to different realizations of firm specific technology shocks, possible leading to default by some firms. The paper advances a new modelling approach for the analysis of financial intermediation and firm defaults that takes account of the financial implications of such defaults for both households and banks. Results from a calibrated version of the model highlight the role of financial institutions in the transmission of credit and technology shocks to the real economy. A positive credit shock, defined as a rise in the loan to deposit ratio, increases output, consumption, hours and productivity, and reduces the spread between loan and deposit rates. The effects of the credit shock tend to be highly persistent even without price rigidities and habit persistence in consumption behaviour.
urn:nbn:de:101:1-201110263708
Keywords: E32; E44; G21; 330; bank credit; financial intermediation; firm heterogeneity and defaults; interest rate spread; real financial linkages; Konjunkturtheorie; Kredit; Technologie; Schock; Finanzintermediär; Dynamisches Gleichgewicht; Insolvenz; Theorie